Experimental study of the passage of canola oil and olive oil droplets between the water-oil interfaces - Safoora Karimi; Ana Abiri; Mojtaba Shafiee (Journal of Food and Bioprocess Engineering, 2022)
Today, the discussion of droplet-fluid interaction is one of the most challenging topics in multiphase (liquid-liquid) flows. In the present study, the behavior of two edible oils (olive oil and canola oil) droplets during the rising in the static fluid of water and passing through the water-oil interface was experimentally investigated. Droplet diameters were controlled in the range of 3.8 to 5.6 mm. First of all, the range of dimensionless numbers was compared to experimental data from other researchers and validated. The results revealed that the droplet shape is elliptical, and that the Weber number decreases in the range of 1 to 2, as the aspect ratio increases. Furthermore, the droplet residence time at the two-phase interface was measured, and the parameters that affected it were examined. Although the results showed that the residence time did not follow a consistent pattern, the conclusion was not far off. Weber dimensionless number was used to introduce hydrodynamic forces and internal surface tension of the droplets. It was shown that none of the theoretical relationships can accurately or even roughly predict the residence time of the oil droplets. Finally, the Weber number has been proven to be dependent on the droplet terminal velocity. Terminal velocity increases with the Weber number and the equivalent diameter.